2023
DOI: 10.1108/bepam-10-2022-0165
|View full text |Cite
|
Sign up to set email alerts
|

Why not reprocessed: identifying factors limiting the uptake of reprocessed structural timber

Abstract: PurposeTimber waste from construction is downcycled into non-structural products, incinerated for energy generation or disposed of in landfills. Existing literature highlights that the use of reprocessed timber for structural purposes is limited. Therefore, this study aims to focus on identifying factors limiting reprocessed structural timber (RST) uptake amongst construction professionals in Australia.Design/methodology/approachCurrent literature shows that the use of reprocessed materials (RMs) depends on us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The findings regarding diverse stakeholders' perceptions of using PwRC in construction projects align with prior research conducted in various regions, including China (Henry and Kato, 2012;Jin et al, 2017), New Zealand (Balador, 2020) and Australia (Tennakoon et al, 2023) itself. Tennakoon et al (2023) reported that while clients are primarily concerned about the cost, construction practitioners focus more on risks associated with the use of PwRC. These findings clearly illustrate the intricate decision-making landscape within the building and construction sector.…”
Section: Comparative Analysis Of the Research Findingssupporting
confidence: 76%
See 3 more Smart Citations
“…The findings regarding diverse stakeholders' perceptions of using PwRC in construction projects align with prior research conducted in various regions, including China (Henry and Kato, 2012;Jin et al, 2017), New Zealand (Balador, 2020) and Australia (Tennakoon et al, 2023) itself. Tennakoon et al (2023) reported that while clients are primarily concerned about the cost, construction practitioners focus more on risks associated with the use of PwRC. These findings clearly illustrate the intricate decision-making landscape within the building and construction sector.…”
Section: Comparative Analysis Of the Research Findingssupporting
confidence: 76%
“…The findings regarding diverse stakeholders' perceptions of using PwRC in construction projects align with prior research conducted in various regions, including China (Henry and Kato, 2012; Jin et al ., 2017), New Zealand (Balador, 2020) and Australia (Tennakoon et al ., 2023) itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations